An optical investigation of dual fuel and RCCI pilot ignition in a medium speed engine - Menno Merts (Elsevier, 2021)
Driven by the Paris agreement and tightening IMO regulations, the marine sector is focusing on lowering engine emissions and moving to low-carbon fossil or renewable fuel such as methane. The dual-fuel concept allows the usage of methane as main energy-source in diesel engines. A small pilot diesel injection acts as an ignition source for the premixed methane. It was investigated how NOx formation, mainly taking place during combustion of the pilot fuel, could be minimized.To better understand the process of ignition of a pilot injection in dual-fuel engines, optical research has been performed on a medium speed dual fuel marine engine. A unique Bowditch 200 mm single cylinder setup enabled high speed recordings of natural luminescence. Both Reactivity Controlled Compression Ignition (RCCI) and Conventional Dual Fuel (CDF) combustion was investigated. The RCCI combustion was created by an early pilot injection, allowing a long mixing time. The CDF cases had a late injection timing.In RCCI operation the higher degree of premixing was recognized by combustion luminescence starting further away from the injector, at a varying location. The diluted pilot combustion generated a limited brightness. The heat release profile was Gaussian/bell-shaped, without the typical diesel premixed peak. In CDF operation the recorded images show that combustion follows the shape of the diesel injector jet. The heat release profile was showing a strong initial peak, resembling the premixed peak known from conventional diesel combustion. This heat release peak in CDF combustion, correlated to NOx emissions, is absent in RCCI mode.